The Environmental Education to Transform Student Behavior from the Classroom (Docentes 2.0 Journal, 2024)
Environmental education is a contemporary topic that has had the gaze of important leaders and researchers to achieve the mitigation of various environmental problems. The trial's objective was to comparatively analyze the receptivity of environmental education received by high school students in two public schools in Colombia. It is framed under the inductive method in the humanistic paradigm, with a mixed, interpretive approach and topical narrative design. It deploys a critical analysis of the knowledge and environmental behavior of students who have received environmental education and those who have yet to. It concludes with the paradox between the theoretical education received by students in the classroom and the environmental behaviors defined by the students' habits manifested in their daily lives, proposing the implementation of pedagogical strategies from the emotionality of the young person to transcend environmental education toward the student's behavior.
Keywords: Environmental Education; Student Behavior; Environment